Biodeterioration of polyethylene by jellyfish nematocyst protein. (March 2023) - Nisa, S. Amreen; Vasantharaja, R.; Supriya, S.; Inbakandan, D.; Dharani, G.; Govindaraju, K.
Abstract: Plastic pollution is one of the major global problems existing now-a-days and has become a cause of serious concern in coastal and marine ecosystems. Increased accumulation of plastics in the aquatic environment by anthropogenic sources results the alteration of the aquatic ecosystem and its functioning. Several variables have an impact on biodegradation, ranging from microbe species to polymer type, physicochemical qualities, and environmental circumstances. The present study was attempted to investigate polyethylene degradation ability of nematocyst protein extracted from the lyophilized nematocyst samples using three different mediums such as distilled water, Phosphate buffered saline (PBS), and seawater. The biodeteriorization potential of nematocyst protein and its interaction with the polyethylene was studied using ATR-IR, phase contrast bright-dark field microscope, and scanning electron microscopic studies. The results uncover the biodeteriorization of polyethylene by jellyfish nematocyst protein without any external physicochemical process and provide evidence for further research. Highlights: Jellyfish nematocyst protein was extracted using distilled water, PBS, and seawater. Biodeteriorization of polyethylene by nematocyst venom protein was observed. FTIR, Phase contrast, and SEM have confirmed the biodeteriorization of polyethylene. Jellyfish nematocyst protein has the potential to mitigate pollution from the ocean.